Relationship Between Physical-Physiological and Psychological Responses in Amateur Soccer Referees - Castillo-Rodríguez A; López-Aguilar J; Alonso-Arbiol I (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The soccer referee confronts stressful situations during the sports competition while performing physical actions of great demand to be close to the play that entails a high physiological demand. The aims of this study are to know the different physical, physiological and psychological responses and their interrelations in real competition in amateur soccer referees and to analyze the effect of the refereed category with the psychological characteristics related to performance. Fifteen referees belonging to the Andalusian Committee of Soccer Referees participated and data were collected in 21 matches of their respective leagues during the 2016-2017 season. The results indicated that the referees have a minor physiological response in the second part of the match, have greater somatic anxiety and lower self-confidence, stress control, motivation, mental ability and team cohesion in competitive matches compared to the baseline sample (p < .05). There are several psycho-physiological correlations between stress control with heart rate less than 80% (positive) and heart rate greater than 80% (negative) (p < .05). In conclusion, the amateur soccer referee is exposed to stress situations, which, the control of it, is related to the physiological responses produced in competition, so that referees with less stress control develop more physiological responses in competition, which can cause decisions with a high degree of fatigue. These findings may advise the soccer referee to supplement training with psychological intervention programs to increase stress control.